Genetic Engineering An Insight into the Strategies and Applications - Jamal, Farrukh (IntechOpen, 2016)
This collection presents various interesting aspects of genetic engineering. Many thought-provoking queries like "Is gene revolution an answer to the world hunger? Do GM crops with more complex transformation contribute to the enrichment of multinationals? Why the US increases food aids?" have been analyzed. Transformation protocols and retrieval of recombinants are essential to the success of genetic engineering. The book throws light on new transformation strategies which can be used to increase the transformation efficiency in most plant species. Genetic engineering offers potentially viable solution to look for alternatives beyond Bt toxins with similar pattern of toxicity. An interesting chapter is dedicated to in vitro fig regeneration and transformation systems. To address the long juvenile phase of fruit trees, the book includes a chapter on plant breeding technique that can significantly shorten the breeding periods. The book dwells on aspects of genome editing which will enable researchers to produce transgenic plants in a more convenient and safer way to genetic modification of stem cells holding significant therapeutic promise to treat complications of diabetes and obesity. I hope this book will serve as a seed for further investigations and novel innovations in the area of genetic engineering.